Perkembangan Teknologi Alat Berat di Era Konstruksi 4.0 - Amalia Rizka Sugiarto; Mochamad Malik Abdulah Saripudin; Dicki Dian Purnama (FORUM MEKANIKA, 2023)
The development of construction 4.0 is now increasing, the challenges that must be faced are increasingly diverse and complex. One of the significant challenges is the problem of increasing productivity, this problem occurs because of the increasing demand for infrastructure. The use of machine construction technology provides new opportunities for more efficient, smart and connected work. Several previous studies have discussed heavy equipment technology in the construction industry, such as analysis of the productivity of heavy equipment working time, implementation of construction automation, comparison of the productivity of manual and automated construction projects. The purpose of this study is to find out whether the development of heavy equipment adapts to the need for technological developments in the construction era 4.0. This study uses simple stages where after the literature is obtained, an analysis of the results of the literature obtained is carried out and validation is carried out by observing the object of research. Based on the analysis, it was concluded that 50% of the development of heavy equipment had matched the need for technological developments in the construction era 4.0. So this is a positive signal in increasing productivity which is the main problem in construction projects. Then the hope for the future is that all providers and users in the construction industry will always make continuous improvements to achieve an integrated infrastructure in the future.